2022
DOI: 10.1111/jfpp.16495
|View full text |Cite
|
Sign up to set email alerts
|

Potential sanitizers and disinfectants for fresh fruits and vegetables: A comprehensive review

Abstract: Fruits and vegetables are being eaten date back to primordial times, ultimately merging with farming, abandoning hunting and gathering.Fruits and vegetables are rich in various important micronutrients for example, vitamin A and C, folic acid, carotenoids, polyphenols, anthocyanins, and antioxidants, and are used in ancient Ayurvedic medical systems to treat different illnesses and ailments (Liguori et al., 2018).Raw fruits and vegetables have high water content and are perishable. They have a wide range of ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 147 publications
0
9
0
Order By: Relevance
“…Complete removal or inactivation of microorganisms during the washing and initial sanitization stage is usually achieved with the combination of ultrasound and other methods, such as heat, pressure, and the addition of sanitizers. The efficacy of the process depends on several factors, such as the resistance of the microorganisms to ultrasound, processing time, surface topology, and ultrasonic power density [57] , [58] , [59] .…”
Section: Goals #14 and #15 – “Life Below Water” And “Life On Land”mentioning
confidence: 99%
“…Complete removal or inactivation of microorganisms during the washing and initial sanitization stage is usually achieved with the combination of ultrasound and other methods, such as heat, pressure, and the addition of sanitizers. The efficacy of the process depends on several factors, such as the resistance of the microorganisms to ultrasound, processing time, surface topology, and ultrasonic power density [57] , [58] , [59] .…”
Section: Goals #14 and #15 – “Life Below Water” And “Life On Land”mentioning
confidence: 99%
“…Commonly, a chlorine‐based solution (sodium or calcium hypochlorite) is used for washing FFVs (Chinchkar et al., 2022). However, studies have demonstrated that chlorine is ineffective against spores and viruses (Gerba et al., 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have demonstrated that chlorine is ineffective against spores and viruses (Gerba et al., 2002). The effectiveness of chlorine is influenced by pH, temperature, FFVs type, and initial microflora population (Chinchkar et al., 2022). Additionally, FFVs washed with 100–200 mg L −1 of chlorine are rejected by European markets because of health and environmental concerns (Deng et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the production processes of these products, at least one disinfection step is typically required, often carried out using chlorine aqueous solutions. However, the use of chlorine disinfection leads to the formation of carcinogenic and toxic by‐products, which have detrimental effects on both the environment and human health (Chinchkar et al, 2022; Deng et al, 2020). Additionally, this step consumes significant amounts of water (Ignat et al, 2015), increasing the water footprint of the process and impacting the sustainability of the agri‐food chain.…”
Section: Introductionmentioning
confidence: 99%